Comparative performance evaluation of Dahlem Red, native and their crosses under intensive management in Himachal Pradesh - DINESH, KRISHANENDER; SANKHYAN, V; THAKUR, Y P; THAKUR, D; KUMAR, R (The Indian Journal of Animal Sciences, 2021)
The present study compared the production performance of DR, Native, DN and DND crosses under intensive system of management. DN and DND crosses showed better growth and production performance compare to local Native parent birds. DND (75% DR inheritance) chicken performed better than DN cross (50% DR inheritance). The better performance of crosses indicated effective utilization and propagation under rural poultry farming system as low input technology birds. It is more beneficial to rear the crosses than local Native birds in Himachal Pradesh. Based on better performance of DND than DN, the former was recommended for development and propagation of Himsamridhi; location specific poultry variety. There is need for wider propagation of these birds in the state by development agencies. Future efforts are required for adaptability assessment of Himsamridhi birds in different agroclimatic region of the state under prevalent village poultry farming system. This will ascertain the suitability of developed cross at farmer’s level.